2004
DOI: 10.1063/1.1756682
|View full text |Cite
|
Sign up to set email alerts
|

Scanning ferromagnetic resonance microscopy and resonant heating of magnetite nanoparticles: Demonstration of thermally detected magnetic resonance

Abstract: Articles you may be interested inSize dependent ferromagnetic resonance and magnetic anisotropy of hexagonal barium and strontium ferrite powders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…If one tries to obtain the increase in temperature of the same order of magnitude through only static field, an enormously high magnetic field of $10 6 Oe would be required. Experimentally measured increase in temperature in case of Fe 3 O 4 is also of the same order in magnitude [8]. Moreover, for the purpose of hyperthermic oncology, the increase in temperature of same order of magnitude is required [22].…”
Section: Calculation Of Relaxation Timementioning
confidence: 96%
See 1 more Smart Citation
“…If one tries to obtain the increase in temperature of the same order of magnitude through only static field, an enormously high magnetic field of $10 6 Oe would be required. Experimentally measured increase in temperature in case of Fe 3 O 4 is also of the same order in magnitude [8]. Moreover, for the purpose of hyperthermic oncology, the increase in temperature of same order of magnitude is required [22].…”
Section: Calculation Of Relaxation Timementioning
confidence: 96%
“…Goennenwein et al estimated the change in electrical properties of ferromagnetic materials due to ferromagnetic resonance [7]. Sakran et al demonstrated the localized heating of magnetite nanoparticles via ferromagnetic resonance and reported the rise in temperature [8].…”
Section: Introductionmentioning
confidence: 98%
“…[29][30][31] Microwave scanning probes have been used in this context for the local ferromagnetic resonance studies. [32][33][34][35][36] Notwithstanding the above comments, there have been only a few attempts in analyzing nanostructures by considering SWS ͑see for example, recent work 37,38 and references therein͒.…”
Section: Introductionmentioning
confidence: 97%
“…While most of the existing microwave probes focus on the measurements of the conductivity and dielectric constant, our probe was utilized for studying physical properties including local, contactless, and non‐destructive spectroscopy such as electron spin resonance, 12 ferromagnetic resonance, 13 and standing spin wave resonance 14 . In addition, our probe allows mapping of (a) surface resistivity, (b) thickness, and (c) Hall effect 15 .…”
Section: Introductionmentioning
confidence: 99%